Global brain volume reductions in a sub-chronic phencyclidine animal model for schizophrenia and their relationship to recognition memory. (October 2019) - Doostdar, Nazanin; Kim, Eugene; Grayson, Ben; Harte, Michael K; Neill, Joanna C; Vernon, Anthony C
Background: Cognitive deficits and structural brain changes co-occur in patients with schizophrenia. Improving our understanding of the relationship between these is important to develop improved therapeutic strategies. Back-translation of these findings into rodent models for schizophrenia offers a potential means to achieve this goal. Aims: The purpose of this study was to determine the extent of structural brain changes and how these relate to cognitive behaviour in a sub-chronic phencyclidine rat model. Methods: Performance in the novel object recognition task was examined in female Lister Hooded rats at one and six weeks after sub-chronic phencyclidine (2 mg/kg intra-peritoneal, n= 15) and saline controls (1 ml/kg intra-peritoneal, n= 15). Locomotor activity following acute phencyclidine challenge was also measured. Brain volume changes were assessed in the same animals using ex vivo structural magnetic resonance imaging and computational neuroanatomical analysis at six weeks. Results: Female sub-chronic phencyclidine-treated Lister Hooded rats spent significantly less time exploring novel objects ( p< 0.05) at both time-points and had significantly greater locomotor activity response to an acute phencyclidine challenge ( p< 0.01) at 3–4 weeks of washout. At six weeks, sub-chronic phencyclidine-treated Lister Hooded rats displayed significant global brain volume reductions ( p< 0.05; q< 0.05), without apparent regional specificity. Relative volumes of the perirhinal cortex however were positively correlated with novel object exploration time only in sub-chronic phencyclidine rats at this time-point. Conclusion: A sustained sub-chronic phencyclidine-induced cognitive deficit in novel object recognition is accompanied by global brain volume reductions in female Lister Hooded rats. The relative volumes of the perirhinal cortex however are positively correlated with novel object exploration, indicating some functional relevance.